Perforation of descending colon diverticulum by swallowed rabbit bone - a case report - Kriegler, T; Majernik, J; Ninger, V (Rozhledy v chirurgii, 2021)
Authors present a case of a 58-year old pacient that underwent acute surgery for perforation of descending colon diverticulum by swallowed rabbit bone. The thesis focuses only on foreign bodies swallowed by adult patients. Comprehensive spectrum of foreign bodies that have entered the digestive tract in another way is omitted.
Keywords: perforation; Adult; foreign bodies; Peritonitis; diverticulosis of colon; Foreign Bodies; zvířata; Diverticulum, Colon; Humans; králíci; perforace střeva; Rabbits; divertikl tlustého střeva; cizí tělesa; dospělí; intestine perforation; Intestinal Perforation; foreign body; lidé; Animals